- #1

strawman

- 5

- 0

- TL;DR Summary
- Should be a simple chain rule problem I think.

y(x,t) = 1/2 h(x-vt) + 1/2 h(x+vt)

This is from the textbook "quantum mechancs" by Rae.

The derivative is given as dy/dt = -v1/2 h(x-vt) + v1/2 h(x+vt)

I'm not quite sure how this is? If I use the chain rule and set the function h(x-vt) = u

Then by dy/dt = dy/du x du/dt I will get (for the first part):

dy/du = 1/2

du/dt = -v

dy/dt = -1/2 v

I've obviously misunderstood this somewhere, being a bit rusty on my calculus. Where have I gone wrong?

Thanks!

This is from the textbook "quantum mechancs" by Rae.

The derivative is given as dy/dt = -v1/2 h(x-vt) + v1/2 h(x+vt)

I'm not quite sure how this is? If I use the chain rule and set the function h(x-vt) = u

Then by dy/dt = dy/du x du/dt I will get (for the first part):

dy/du = 1/2

du/dt = -v

dy/dt = -1/2 v

I've obviously misunderstood this somewhere, being a bit rusty on my calculus. Where have I gone wrong?

Thanks!